2018
DOI: 10.1371/journal.pone.0202971
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and misconceptions towards sharks and shark meat consumption along the Peruvian coast

Abstract: Misconceptions, lack of knowledge, and negative attitudes towards sharks act as barriers preventing actions required to tackle threats to shark populations, limiting the success of global shark conservation initiatives. Peru, a major player for the international trade of shark products, recently approved the ‘National Action Plan for the Conservation and Management of Sharks, Rays and Chimaeras’ (PAN-Tib); a guiding document for conservation initiatives aimed at these fishes. Within PAN-Tib, the assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
0
6
1
1
Order By: Relevance
“…This is a clear indicator that legislation and policy is not a major factor that could affect and shape people's knowledge and attitude towards biodiversity and conservation. The results also showed that gender, age and level of education do not affect elasmobranch-related knowledge and attitude which is contrary to some other studies (O'Bryhim & Parsons, 2015;Tsoi et al, 2016;Lama et al, 2018;Alfonso et al, 2021). Marine-related education and marine-related activities were the strongest predictors of a participant's knowledge and attitude towards elasmobranchs.…”
Section: Drivers Of Elasmobranch Knowledge and Effects On Attitudecontrasting
confidence: 91%
“…This is a clear indicator that legislation and policy is not a major factor that could affect and shape people's knowledge and attitude towards biodiversity and conservation. The results also showed that gender, age and level of education do not affect elasmobranch-related knowledge and attitude which is contrary to some other studies (O'Bryhim & Parsons, 2015;Tsoi et al, 2016;Lama et al, 2018;Alfonso et al, 2021). Marine-related education and marine-related activities were the strongest predictors of a participant's knowledge and attitude towards elasmobranchs.…”
Section: Drivers Of Elasmobranch Knowledge and Effects On Attitudecontrasting
confidence: 91%
“…Also, education level had little contribution to perception improvement among people with positive prejudice because this group generally exhibited good knowledge and positive perceptions toward sharks. These trends sustain the leverage of the emotional component on the regulation of human attitudes toward sharks (Tsoi et al, 2016;Lama et al, 2018) and suggest that considerable improvements in perceptions could be achieved by resolving the prevalence of unjustified feelings and prejudice resulting from societal misconceptions about these species. Augmenting the specific FIGURE 4 | Effects of the interaction of education level (i.e., elementary, high, and superior education) with specific knowledge about sharks (i.e., low, medium, and high) on the variability in perceptions toward sharks, assessed with a Likert-based ordered logistic regression model.…”
Section: Discussionmentioning
confidence: 81%
“…A most relevant relationship between education level, knowledge about and perceptions toward sharks was evidenced in this study, with increased education and knowledge generally benefiting more positive perceptions. Previous research also associated higher education level with greater knowledge about sharks and more positive perceptions and attitudes toward these species (Thompson and Mintzes, 2002;O'Bryhim and Parsons, 2015;Tsoi et al, 2016;Lama et al, 2018). Misperceptions may derive from a lack of acquaintance with and understanding about sharks, rendering people susceptible to misinformation (Muter et al, 2012;Myrick and Evans, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Attitudes, which refer to an individual's evaluation of a person, concept, entity or action, can help predict human behaviour and determine participation in conservation activities (Ajzen, 1991; Solomon et al, 2012; Sponarski et al, 2014). The attitudes of fishers and the general public towards sharks present both challenges and opportunities for effective shark conservation (Ali et al, 2020; Drymon & Scyphers, 2017; Glaus et al, 2018; López de la Lama et al, 2018). Fishers also tend to perceive marine species holistically and as groups, rather than individual species (Karnad, 2022).…”
Section: Introductionmentioning
confidence: 99%